2010
DOI: 10.1016/j.virol.2010.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Frog virus 3 ORF 53R, a putative myristoylated membrane protein, is essential for virus replication in vitro

Abstract: Although previous work identified 12 complementation groups with possible roles in virus assembly, currently only one frog virus 3 protein, the major capsid protein (MCP), has been linked with virion formation. To identify other proteins required for assembly, we used an antisense morpholino oligonucleotide to target 53R, a putative myristoylated membrane protein, and showed that treatment resulted in marked reductions in 53R levels and a 60% drop in virus titers. Immunofluorescence assays confirmed knock down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…In CyHV-3 and WSSV, the envelope proteins are composed of many highly abundant viral proteins. However, iridoviruses have a different virion structure with an innermost protein-DNA core, an internal lipid membrane, an icosahedral capsid, and, in some cases, viral envelope (4,34). The current study also shows that envelopes in ISKNV are composed of a limited number of low-abundance viral proteins.…”
Section: Discussionmentioning
confidence: 59%
“…In CyHV-3 and WSSV, the envelope proteins are composed of many highly abundant viral proteins. However, iridoviruses have a different virion structure with an innermost protein-DNA core, an internal lipid membrane, an icosahedral capsid, and, in some cases, viral envelope (4,34). The current study also shows that envelopes in ISKNV are composed of a limited number of low-abundance viral proteins.…”
Section: Discussionmentioning
confidence: 59%
“…Perceived diffi culty in obtaining antibodies is often mentioned as the reason for not incorporating it as part of the basic laboratory testing. Primarily, IHC has been used in research studies and often the investigators develop their own antibodies or obtain them from other researchers (e.g., Hyatt et al 2002 ;Cunningham et al 2008 ;Balseiro et al 2009Balseiro et al , 2010Bayley et al 2013 ;Whitley et al 2010 ;Chinchar et al, 1984 ). This technique may be especially useful to identify inclusion bodies within areas of necrosis, as this can be challenging when abundant cellular debris is present (Fig.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…During the procedure, multiple photos are taken and reconstructed to yield a 3D image of the virus. Researchers have been using cryo-EM to evaluate the role of various surface proteins in viral assembly and replication (see Yan et al 2009 ;Whitley et al 2010 ;Tran et al 2011 ). It is possible that these fi ndings may provide insight into treatment protocols or vaccine development.…”
Section: Electron Microscopymentioning
confidence: 99%
“…RGV 53R is a core gene in iridoviruses, and encodes a viral envelope protein that plays an important role in virus assembly and infection [73,74]. Recently, we have chosen RGV 53R as a target gene to construct a conditional lethal recombinant RGV (i53R-RGV-lacIO) containing the inducible lac repressor/operator system that can be regulated by IPTG, and have found that the 53R expression level, plaque formation ability and viral titers in i53R-RGV-lacIO are significantly reduced in the absence of IPTG.…”
Section: Important Core Genes and Their Functions In Iridovirusesmentioning
confidence: 99%